2020
DOI: 10.31364/scirj/v8.i4.2020.p0420763
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Voice of Women in Marine and Maritime Industry

Abstract: Marine and maritime industry often have been acknowledged as male-dominated. Women represent nearly 2% of the workforce in the maritime community. Even though, the marine and maritime industry have been evolving throughout history, women's placement in it has not been notorious. Women are seldom neglected from the global industry for being family-committed and/ or being considered as weaker sex. Yet women play major roles in sustainable development hence they should be incorporated in ocean-based policy, gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Barbare (2014) reveals that 94% of women work on passenger ships, with 68% on ferries and 26% on cruise ships. Meanwhile, 6% work on cargo ships (Arulnayagam, 2020). Based on the 2021 BIMCO/ICS Seafarers Report, if presented with numbers, the number of female workers in the maritime sector worldwide is estimated to be only around 24,059 (International Maritime Organization, n.d.) from the total number of women in the world, 3.95 billion (Annur, 2023).…”
Section: Despitementioning
confidence: 99%
“…Barbare (2014) reveals that 94% of women work on passenger ships, with 68% on ferries and 26% on cruise ships. Meanwhile, 6% work on cargo ships (Arulnayagam, 2020). Based on the 2021 BIMCO/ICS Seafarers Report, if presented with numbers, the number of female workers in the maritime sector worldwide is estimated to be only around 24,059 (International Maritime Organization, n.d.) from the total number of women in the world, 3.95 billion (Annur, 2023).…”
Section: Despitementioning
confidence: 99%
“…According to Chapman and Mishra (2019) and Kitada and Langåker (2016), the marine transport sector's unprecedented investment and expansion have not accelerated with the progress of women's employment and leadership in the industry. Female labor force participation in the maritime sector stands at an estimated 27%-28% compared to over 90% for men, especially on merchant vessels (Ahalya 2020;Lares 2017).…”
Section: Perceptions and Attitudes Of Women's Employment And Leadersh...mentioning
confidence: 99%
“…This is the reason women are undermined, misjudged and ill-treaded when they foray into a male-bastion. Furthermore, Abdelall (2008) as cited in Arulnayagam (2020), attributed the unwelcomed presence of women onboard based on superstitions that women would be "potential source of malevolence or bad luck". The present study revealed that men counterparts of the participants are not comfortable having women in their workplace, like the ship.…”
Section: Cultural Adaptationmentioning
confidence: 99%